Investigating the Philosophical View of Teaching Circles Theorem - Asare, Bright (Mathematics Education Journal, 2024)
Circle theorem was seen as the most challenging mathematics topic most students’ in Ghana run away from. During the WASCE, most students run away from answering mathematics questions that are in line with circle theorem. Such challenge has drawn the attention of mathematics teachers and researchers in mathematics education to find out the factors that drives students from attempting circle theorem question and the appropriate approach that can be used to teacher and to solve questions in circle theorem. The study aimed to investigate the philosophical view of teaching circle theorem. The literature review was based on ontological view of circle theorem, axiological view of circle theorem, and epistemological view of circle theorem. The study concluded that, the three philological view of mathematics has a unique significant effect on teaching and learning circle theorem.